Efektifitas Partisipasi Finansial Masyarakat dalam Lembaga Pendidikan Islam: Studi Kasus Di Yayasan GUPPI Lamongan - Madekhan Madekhan; Winarto Eka Wahyudi (Indonesian Journal of Islamic Education Studies (IJIES), 2020)
In the context of education, the whole of society has the possibility to contribute financially to the funding of education. Researchers found this type of participation through the Islamic Education Reform Movement Foundation (GUPPI) as an educational organization that has consistently collected and managed budgets from student guardians to ensure the availability of salaries for teachers and employees at MI Islamiyah Dinoyo. Through a mixed research method with a chain exploration, design, this study seeks to analyze the effectiveness of the management of community financial participation by the Dinoyo GUPPI Foundation in supporting education funding at MI Islamiyah Dinoyo. The results showed that the successful management of public financial participation was supported by the application of the principles of openness, voluntaries, affirmation to poor households, and maintaining the principles of justice. Meanwhile, the effectiveness of the results of the management of community financial participation by the GUPPI Dinoyo Foundation is evidenced by the payment of salaries and allowances for teachers and employees of MI Islamiyah Dinoyo which reaches 92% of the funds raised.